Roman Women’s Dress - Radicke, Jan (2022)
The book concerns female dress in Roman life and literature. The main focus is on female Roman dress as it may have been worn in daily life in Rome and in a social environment influenced by Roman culture in the time from the beginnings of the Republic until the end of the 2nd century AD.